Universitas Islam Negeri (UIN) Telaah Ontologis, Epistemologis Dan Aksiologis - Oktrigana Wirian (Yayasan Rahmat Islamiyah, 2022)
This article was written in the context of constructing the concepts of ontology, epistemology, and axiology which are intended as a foundation in the philosophy of Islamic Higher Education in Indonesia. Specifically looking at the State Islamic University (UIN). The type of writing in the article is qualitative research using library research with content analysis method as a data analysis tool. The description of the results of this article, namely the struggle to combine through an integrated model has been initiated by the State Islamic University, but the readiness of supporters in this regard such as infrastructure, human resources, and others is still being formed. Furthermore, the task assigned by the government is the main task in advancing education, especially Islamic education which includes opportunities as well as challenges.